2018
DOI: 10.1111/sji.12711
|View full text |Cite
|
Sign up to set email alerts
|

Decreased regulatory function of CD4+CD25+CD45RA+ T cells and impaired IL‐2 signalling pathway in patients with type 2 diabetes mellitus

Abstract: In this study, the frequency and function of CD4+CD25+CD45RA+ regulatory T cells (Treg) and intracellular IL‐2 signalling molecules in patients with type 2 diabetes mellitus (T2DM) were investigated. Tregs and responder T cells (Tresp, CD4+CD25− T cells) were sorted and suppression assays were performed using flow cytometry. Phosphorylation of signal transducer and activator of transcription‐5 (pSTAT5) were assessed using flow cytometry. Gene expression of FOXP3 was performed with the SYBR green Real Time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This may elevate the immunosuppressive activity of Treg cells, and compromise the immune response of T lymphocytes to pathogen. Thus, IL-2 mediated regulation of CD4+CD25+Foxp3 Treg cells via STAT5 pathway may play a key role in the development of COM (2)(3)(4)(5). To date, little is known about the role of IL-2/STAT5/CD4+CD25+Foxp3 Treg pathway in the pathogenesis of COM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may elevate the immunosuppressive activity of Treg cells, and compromise the immune response of T lymphocytes to pathogen. Thus, IL-2 mediated regulation of CD4+CD25+Foxp3 Treg cells via STAT5 pathway may play a key role in the development of COM (2)(3)(4)(5). To date, little is known about the role of IL-2/STAT5/CD4+CD25+Foxp3 Treg pathway in the pathogenesis of COM.…”
Section: Introductionmentioning
confidence: 99%
“…However, in control group, the bone tissues were closely arrangement, and there was no obvious bone destruction and infiltration of inflammatory cells in the medullary cavity (17). A variety of studies have shown the expression of IL-2 in the serum increases in patients with COM and COM animals (2)(3)(4)(5). Therefore, at different time points, the blood was collected for the detection of serum IL-2 concentration.…”
mentioning
confidence: 99%
“…It has been suggested that there is a reduced immunosuppressive function of Tregs due to impaired IL-2 signalling in T1D (24-28), a defect which may subsequently lead to a more aggressive immune destruction of pancreatic b cells by T EFF (12,28). In addition, defects in the intracellular IL-2 pathways and a decreased regulatory function have recently been reported in patients with type 2 diabetes (T2D) (29). In many autoimmune diseases, such as multiple sclerosis (MS) (30), rheumatoid arthritis (31), primary Sjögren's syndrome (32), scleroderma (33), and inflammatory myopathies (34), but also in various cancers (31), sIL-2R has been proposed to be a biomarker for disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Zahra Telikani (M.Sc) 1,2 , Vida Sheikh (M.D) 3 , Alireza Zamani (Ph.D) 1,2 , Shiva Borzouei (M.D) 3 , Iraj Salehi (Ph.D) 4 , Mohammad Ali Amirzargar (M.D) 3 , Mahdi Alahgholi-Hajibehzad (Ph.D) *1,2 Introduction: Type 2 diabetes mellitus (T2DM) is an inflammatory disease with alterations in immune system. Remarkably, cytokine imbalance plays an important role in pathogenesis of T2DM.…”
Section: Effect Of Sitagliptin On Serum Levels Of Tnf-α Il-1β and Il-10 In Patients With Type 2 Diabetes Mellitusmentioning
confidence: 99%